Rh(iii)-catalyzed synthesis of tetracyclic isoquinolinium salts via C–H activation and [4+2] annulation of 1-phenyl-3, 4-dihydroisoquinolines and alkynes in ethanol. Issue 52 (24th August 2018) - Dang, Xinxin; He, Yu; Liu, Yingtian; Chen, Xuehong; Li, Jun-Long; Zhou, Xian-Li; Jiang, Hezhong; Li, Jiahong
Abstract : An efficient method to construct tetracyclic isoquinolinium salts via C–H activation and [4 + 2] annulation reactions in ethanol is described. Abstract : An efficient and convenient method to construct tetracyclic isoquinolinium salts via [Cp*RhCl2 ]2 catalyzed C–H activation and [4 + 2] annulation reactions in ethanol is described. This reaction is very fast and highly efficient in the green solvent ethanol. The reaction works with a broad substrate scope affording the products in good to excellent yields in a short time. Moreover, a ratio of S/C up to 10 000 could be achieved with gram scale synthesis.